2018
DOI: 10.3390/ma11091549
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-Ionic Nanocomposite La0.1Sr0.9MnO3−δ-Ce0.8Sm0.2O2−δ Functional Layer for High Performance Low Temperature SOFC

Abstract: A novel composite was synthesized by mixing La0.1Sr0.9MnO3−δ (LSM) with Ce0.8Sm0.2O2−δ (SDC) for the functional layer of low temperature solid oxide fuel cell (LT-SOFC). Though LSM, a highly electronic conducting semiconductor, was used in the functional layer, the fuel cell device could reach OCVs higher than 1.0 V without short-circuit problem. A typical diode or rectification effect was observed when an external electric force was supplied on the device under fuel cell atmosphere, which indicated the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To increase the electrochemical activity of LSM air electrodes, their compositions with ionic conductors were applied, e.g., with solid electrolytes (YSZ [205,303,352,[372][373][374][375][376][377][378][379][380][381][382][383], YSZ with GDC10 [374], SSZ [149,[384][385][386][387][388][389][390], GDC10 [391], GDC [152,198], SDC [148,149,387,392,393], doped Bi 2 O 3 [151,[394][395][396][397][398][399], BaZr 0.85 Y 0.15 O 3 − δ (BZY15) [154], LWO56 [156], LSGM [400,401]), or MIEC materials (Co- [150,402] and Fe-based perovskites [403][404][405]). The optimu...…”
Section: Enhancement Of the Ionic-conducting Electrode Componentmentioning
confidence: 99%
“…To increase the electrochemical activity of LSM air electrodes, their compositions with ionic conductors were applied, e.g., with solid electrolytes (YSZ [205,303,352,[372][373][374][375][376][377][378][379][380][381][382][383], YSZ with GDC10 [374], SSZ [149,[384][385][386][387][388][389][390], GDC10 [391], GDC [152,198], SDC [148,149,387,392,393], doped Bi 2 O 3 [151,[394][395][396][397][398][399], BaZr 0.85 Y 0.15 O 3 − δ (BZY15) [154], LWO56 [156], LSGM [400,401]), or MIEC materials (Co- [150,402] and Fe-based perovskites [403][404][405]). The optimu...…”
Section: Enhancement Of the Ionic-conducting Electrode Componentmentioning
confidence: 99%
“…Several composite cathodes containing LSM were examined so far [14,. The second phase was reported: (i) the electrolyte material of pure ionic conductivity such as yttria-stabilized zirconia (YSZ) [16][17][18][19][20][21], scandia-stabilized zirconia [22], gadolinia-doped ceria (GDC) [18,23] samaria-doped ceria (SDC) [24], bismuth oxide conductors [25][26][27], and lanthanum tungstate [28]; (ii) the noble metal of high catalytic activity such as silver [29][30][31] and platinum [28]; (iii) material of mixed ionic electronic conductivity such as LSCF [14,32], La 0.6 Sr 0.4 FeO 3−δ , (LSF) [31], La 2 Ni 0.5 Co 0.5 O 4 , and LaNi 0.5 Co 0.5 O 3 [33]; others such as BaO [34], CeO 2 [31], CoO x [35], Co 3 O 4 [36,37], and FeO x [38].…”
Section: Introductionmentioning
confidence: 99%
“…Strandbakke et al [28] reported that composite cathodes LSM with lanthanum tungstate and platinum reveal polarization resistance 40 Ω cm 2 at 650 • C. Rehman et al [18] described the properties of ternary composite LSM-YSZ-GDC, reporting maximum power densities of 215, 316, and 396 mW cm −2 at 750, 800, and 850 • C, respectively. Wang et al [24] applied LSM-SDC composite cathode in low-temperature SOFC. The authors reported that the optimum ratio of LSM:SDC is 1:2.…”
Section: Introductionmentioning
confidence: 99%
“…These exceptional conductivity values are achieved through the creation of vacancies in their framework. However, there are many examples of SOFC with alternative electrolytes working successfully below 800 °C [8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%